Comparative Analysis Of Arm Muscle Strength Based On Gender In Students Aged 10-12 Years At Sd Muhammadiyah 08, Dau District, Malang Regency - Atika Yulianti; Fajar Abhyasa Abimanyu; Nungki Marlian Yuliadarwati (Journal of Social Research, 2024)
Every child experiences development, development occurs from early age to adulthood. Development is progressive, systematic and sustainable. The things that develop in every child are the same, it's just that there are differences, differences in the speed of development, and there is development that precedes the previous development, even though the development between one aspect and another occurs in tandem. The purpose of this study is to analyze the factors that affect the strength of arm muscles in students aged 10-12 years. This study is a quantitative research that uses a type of observational analytical research with a cross sectional method. The research was conducted in October-November 2023 with a time span starting from October 25, 2023 to November 25, 2023 at SD Muhammadiyah 08, Dau District, Malang Regency, East Java. Based on the research on the strength of students' arm muscles based on the age of 10-12 years, it can be concluded that there is a significant increase in the strength of students' arm muscles in the age range of 10-12 years.